Clinical outcomes of patients treated on the Heidelberg interprofessional training ward vs. care on a conventional surgical ward: a retrospective cohort study - Kuner, Charlotte; Dörr-Harim, Colette; Feißt, Manuel; Klotz, Rosa; Heger, Patrick; Probst, Pascal; Strothmann, Hendrik; Götsch, Burkhard; Schmidt, Jochen; Mink, Johanna; Mitzkat, Anika; Trierweiler-Hauke, Birgit; et al. (Journal of interprofessional care, 2022)
Interprofessional training wards (IPTW) are a form of interprofessional education enabling trainees of different healthcare professions to work together in teams. Concerns about patient safety are a major barrier to the implementation of IPTWs. The objective of this retrospective study was to analyze patient relevant clinical outcomes on Germany’s first IPTW (Heidelberger Interprofessionelle Ausbildungsstation; HIPSTA) in the Department of Surgery at University Hospital Heidelberg in comparison to a conventional surgical ward (CSW). The setting is a large tertiary care center with a focus on major oncological surgery. The endpoints were postoperative complications according to the Dindo-Clavien Classification and a set of patient-safety outcomes.